Tipologi Makam dan Ornamen Nisan pada Kompleks Makam Sunan Ampel Surabaya - Abdur Rahman; Wildayati Wildayati (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
This study aims to determine (1) typology of the tomb of Sunan Ampel and (2) tombstone ornaments on the tomb of X in the tomb complex of Sunan Ampel. This study uses qualitative research methods through techniques (1) observation, (2) interviews, (3) and literature studies. Those data obtained are analyzed using archeological theory and the approach to artistic values. The results of this study are (1) typology of the tomb of Sunan Ampel, consisting of three elements: (a) sepulchre; (b) tombstone; and (b) the grave cupola, while (2) the tombstone ornaments on the tomb of X in the Sunan Ampel tomb complex are: (a) curly motifs, (b) vine decorations, and (c) stump decorations. Overall, it can be seen that the tomb complex of Sunan Ampel has the typology of tombs and tombstone ornaments that have characteristics and meanings in it.